Everywhere and Nowhere: Information Literacy in the Political Science Classroom. Issue 3 (July 2022) - Thornton, Stephen; Atkinson, Douglas B.
ABSTRACT: Recent research suggests that many faculty members believe that their students are lacking the information literacy (IL) skills needed to be successful in their college career. Reports also suggest that there is a broader issue about the uncertain position of IL in the university curriculum. This article uses data from a worldwide survey of political science faculty to better understand how widespread this perception is, what is being done about this perceived problem, and what steps can be taken to encourage faculty to implement IL training in the classroom. We find that faculty believe that there is a problem but many are not explicitly teaching IL as part of their courses. We also find that faculty members who have received IL training are far more likely to include it in their courses. This leads us to suggest that IL training should be provided at the faculty level, which will have positive downstream effects on the IL training that students receive. We also contend that IL deserves a more prominent place in the university curriculum.